Factors associated with successful electrolarynx use after total laryngectomy, a multi‐institutional study - Cassie Pan; Leah I. B. Andrews; Emily Johnson; Neel K. Bhatt; Zain H. Rizvi (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objective To identify characteristics associated with successful electrolarynx (EL) use after total laryngectomy (TL). Methods Records of 196 adults who underwent TL from 03/15/2012 to 03/15/2022 at the University of Washington and Puget Sound Veterans Affairs were reviewed. Characteristics included age, Charlson Comorbidity Index, social support, pre‐operative radiation (RT) and chemoradiation (CRT), and 6‐month post‐TL swallow status. EL success was evaluated using pre‐defined criteria of intelligibility, reliability, and independence with use. Poisson regressions and robust standard error estimates were used to estimate unadjusted risk ratios for each characteristic. Statistically significant characteristics were included in multivariate analysis (MVA) to estimate adjusted risk ratios. Results Median age was 64, median Charlson Comorbidity Index was 5, 170 (87%) were male, 159 (81%) had high social support, and 159 (81%) attained post‐TL full‐oral diet. Pre‐operatively, 110 (56%) had RT, including 55 (28%) with CRT. Ninety‐three (47%) met our criteria for EL success. Characteristics significantly associated with EL success included social support (p = .037) and post‐TL full‐oral diet (p = .037); both approached significance on MVA. EL success varied by pre‐operative treatment on univariate (p = .005) and MVA (p = .014). Compared to no prior RT or CRT, the probability of EL success was 29% higher with prior RT and 29% lower with prior CRT in MVA, although these associations did not reach significance. Conclusions In this retrospective review, EL success correlated with high social support, post‐TL full‐oral diet, and pre‐operative treatment history. These results warrant validation in a larger prospective study to help guide the choice of voice rehabilitation modalities or intensified speech therapy. Level of Evidence 4.